Stages of change for regular physical activity among government employees - Phing, Chee Huei; Abu Saad, Hazizi; Mohd Yusof, Barakatun Nisak; Mohd Taib, Mohd Nasir (University of Pitesti, Romania, 2014)
Problem statement: Changes in lifestyle have led to the rising rate of nutrition-related chronic diseases in Malaysia. Purpose: A cross-sectional study was conducted to identify demographic characteristics and lipid profile by individuals' readiness for regular physical activity. Approach:A total of 675 employees from five government agencies in Putrajaya were selected using multi-stage random sampling.Results: The majority of the participants (46.4%)considered themselves to be physically active. There was no significant association between stages of change and demographic factors, except gender. The adjusted mean body mass index for the Precontemplation/ Contemplation group (27.12±0.27 kg/m^sup 2^) was significantly higher than that of the Preparation/Action group (25.92±0.37 kg/m2) and the Maintenance group (24.71±0.52 kg/m^sup 2^) [F= 9.60; p<0.001]. In addition, there was a statistically significant difference in adjusted mean waist circumference [F= 11.49; p<0.001], waist-to-hip ratio [F= 8.01; p<0.001], HDL cholesterol [F= 11.66, p<0.001] and triglycerides [F= 6.88; p<0.001] between stages of change groups.Conclusions: Gender may play a vital role towards the intention to engage in regular physical activity. Furthermore, anthropometric and some lipid parameters (HDL cholesterol and triglycerides) differ significantly among stages of change groups.